Sharing Christ with the dying : bringing hope to those near the end of life - Rossi, Melody (Minneapolis, Minnesota : Bethany House Publishers, 2014)
"Presents information on how to discuss spiritual matters with someone who is terminally ill. Addresses end-of-life issues, including physical and emotional aspects, as well as grief and loss"--
Previously published as May I Walk You Home?
Keywords: Church work with the terminally ill; Terminally ill -- Religious life; Death -- Religious aspects -- Christianity